Koinokulasi Rhizobium dan Bakteri Pelarut Fosfat pada Tanah Mineral Masam untuk Memperbaiki Pertumbuhan Bibit Sengon - Deni Alfiati (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Co-Inoculation Rhizobium and Phosphate Solubilizing Bacteria on Acid Mineral Soil to Enhance Seedling Growth of SengonABSTRACT. Study of coinoculation between rhizobium and solubilizing phosphate bacteria was done in greenhouse. The aim of the study to find their effect to seedling growth of sengon in Ultisol and Inceptisol. The study used factorial split plot design and three replication. As a treatment were kind of soil and inoculation of rhizobium and phosphate solubilizing bacteria. As a control was not inoculation, with nitrogen fertilizer and phosphate fertilizer. The result showed that co-inoculation between rhizobium and phosphate solubilizing bacteria could enhance seedling growth of sengon in Ultisol and Inceptisol. As compared between co-inoculation and inoculation with rhizobium or phosphate solubilizing alone, showed that the similar result in Ultisol. While Inceptisol, inoculation with Rhizobium and phosphate solubilizing bacteria better than co-inoculation.